Solid State Theory An Introduction - Rössler, Ulrich (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Solid-State Theory - An Introduction is a textbook for graduate students of physics and material sciences. It stands in the tradition of older textbooks on this subject but takes up new developments in theoretical concepts and materials which are connected with such path breaking discoveries as the Quantum-Hall Effects, the high-Tc superconductors, and the low-dimensional systems realized in solids. Thus besides providing the fundamental concepts to describe the physics of electrons and ions of which the solid consists, including their interactions and the interaction with light, the book casts a bridge to the experimental facts and opens the view into current research fields.